The Effect of Pet Insurance on Presurgical Euthanasia of Dogs With Gastric Dilatation-Volvulus: A Novel Approach to Quantifying Economic Euthanasia in Veterinary Emergency Medicine - Boller, Manuel; Nemanic, Tereza S.; Anthonisz, Jarryd D.; Awad, Magdoline; Selinger, Joshua; Boller, Elise M.; Stevenson, Mark A. (Frontiers in Veterinary Science, 2020)
Euthanasia of companion animals in veterinary emergency medicine is a common cause of death. Euthanasia is economic when it is the consequence of the pet owner’s inability to afford essential treatment while a viable medical alternative to euthanasia exists. Gastric dilatation-volvulus (GDV) is an acute life-threatening emergency condition of dogs; if left untreated, rapid death is inevitable. Surgical treatment leads to survival of around 80-90% of dogs; however, such treatment is costly. Therefore, pre-surgical euthanasia may be largely economically motivated. Consequently, having pet insurance, a financial instrument to reduce the burden of unforeseen veterinary medical costs on pet owners, would be expected to abolish the risk for pre-surgical economic euthanasia. We therefore aimed to determine whether pet insurance attenuates the risk of pre-surgical economic euthanasia in dogs with GDV. Non-referred dogs (n = 260) with GDV and known insurance status seen at 24 emergency clinics over a 2-year period were included. Relevant data (e.g., insurance status, age, comorbidities, outcome) were retrospectively extracted from a pet insurer’s claim records (insured animals) or from electronic medical records of participating hospitals (non-insured animals). Forty-one percent of dogs (106 of 260 dogs) did not survive to hospital discharge; 82 (77%) of non-survivors died before surgery, all through euthanasia. The pre-surgical euthanasia rate was 10% in insured and 37% in non-insured dogs (p < 0.001). When adjusted for the effect of age, deposit size, comorbidities and blood lactate concentration, the absence of insurance increased the odds of pre-surgical euthanasia by a factor of 7.4 (95% CI 2.0 to 37; p = 0.002). Of dogs undergoing surgery, 86% survived to hospital discharge. Overall, 80% of insured animals and 53% of non-insured animals survived to hospital discharge (p < 0.001). Thus, insurance markedly decreased the risk of pre-surgical euthanasia indicating that the cause of pre-surgical euthanasia of dogs with GDV is predominantly economic in nature. The rate of pre-surgical euthanasia in dogs with GDV may emerge as a suitable marker to quantify economic decision making of pet owners and to measure the impact of financial interventions aimed at mitigating economic duress associated with cost of veterinary care.